The Influence of Transformational Leadership on Employee Performance: An Emotional Intelligence-Based Approach - Nofiyanti, Nofiyanti; Farhan, Akhmad; Fajrin, Andira; Purwanto, Agus; Kulla Himmy Azz, Istajib; Mintari, Nia (Journal of Industrial Engineering & Management Research, 2025)
This study aims to analyze the influence of transformational leadership on employee performance by considering the role of emotional intelligence as a moderating variable. Transformational leadership style, which includes ideal influence, inspirational motivation, intellectual stimulation, and individual attention, is considered capable of encouraging motivation and work productivity. Meanwhile, emotional intelligence plays a crucial role in fostering harmonious interpersonal relationships and creating a conducive work environment. This study employs a quantitative approach through a survey using a questionnaire administered to 110 respondents from the public sector in East Java, as well as additional samples from the education and Islamic finance sectors. Multiple linear regression analysis shows that transformational leadership has a positive and significant effect on employee performance (β = 0.536; p < 0.01). The moderation test reveals that emotional intelligence strengthens this relationship (β = 0.289; p < 0.05). These findings are reinforced by results from other sectors showing similar effects. The study concludes that the combination of transformational leadership and emotional intelligence synergistically enhances employee performance, loyalty, and job satisfaction. The practical implications of this research emphasize the need for leadership training that not only focuses on managerial skills but also on developing emotional intelligence as a strategy for sustaining organizational effectiveness.